2016
DOI: 10.1016/j.psep.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic treatment technology for palm oil mill effluent (POME) – A review

Abstract: a b s t r a c tThis review provides insight into various techniques utilized for the treatments of palm oil mill effluents (POME). Generally, POME treatment is achieved in two ways, these are (1) pretreatment stages, involving majorly the reduction of oil and grease and suspended matter and (2) an advanced treatment stage, in which wastewater contaminants (e.g. BOD 5 , COD) are reduced to standard discharge limits. Different methods utilized in the treatment of POME such as coagulation-flocculation, anaerobic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 134 publications
1
23
0
1
Order By: Relevance
“…Hybrid processes encompass a systematic combination of the anaerobic, anoxic and aerobic process to improve treatment efficiencies [46,54,160]. Hybrid MBR (HybMBR) provide a platform for anaerobically treated wastewater to undergo aerobic treatment, and this gives the possibility for chains processes such as biodegradation, de-chlorination, nitrification, denitrification as well as filtration process which usually takes place at the membrane section [38].…”
Section: Hybrid (Integrated) Processes In Mbr (Hybmbr)mentioning
confidence: 99%
“…Hybrid processes encompass a systematic combination of the anaerobic, anoxic and aerobic process to improve treatment efficiencies [46,54,160]. Hybrid MBR (HybMBR) provide a platform for anaerobically treated wastewater to undergo aerobic treatment, and this gives the possibility for chains processes such as biodegradation, de-chlorination, nitrification, denitrification as well as filtration process which usually takes place at the membrane section [38].…”
Section: Hybrid (Integrated) Processes In Mbr (Hybmbr)mentioning
confidence: 99%
“…The wide band gap of TiO2 restricts its light absorption in visible light region [28]. TiO2 itself can be classified into different types such as Degussa P25, Millennium PC50, PC100, PC105, PC500 UV100 and TTIP (titanium tetraisopropoxide) [29].…”
Section: Preparation Of Modified Tio2mentioning
confidence: 99%
“…However, this great margin may be due in part to nature of these measurements. The values in Table 1 are obtained from averages presented in several studies [1,34,43] who have also reported values averaged from other studies. There have been researchers reporting POME final discharge values that are orders of magnitudes higher than the DOE discharge limit.…”
Section: Characteristics Of Pomementioning
confidence: 99%
“…Currently a vast majority of palm oil plantations (> 85%) employ aerobic and anaerobic digestion as the preferred method for the removal of much of the COD, BOD and total suspended solids (TSS) in raw POME [45,46]. This is usually preceded by pretreating the raw POME via mechanical and physiochemical processes of which coagulation/flocculation followed by sedimentation and filtration are commonly used [43]. The main purpose of pre-treatment is some removal of COD, total suspended solids (TSS) and turbidity prior to mode advanced treatment geared at reducing the bulk of the organic load.…”
Section: Conventional Pome Treatment Technologymentioning
confidence: 99%